2014
DOI: 10.3389/fgene.2014.00102
|View full text |Cite
|
Sign up to set email alerts
|

CARF and WYL domains: ligand-binding regulators of prokaryotic defense systems

Abstract: CRISPR-Cas adaptive immunity systems of bacteria and archaea insert fragments of virus or plasmid DNA as spacer sequences into CRISPR repeat loci. Processed transcripts encompassing these spacers guide the cleavage of the cognate foreign DNA or RNA. Most CRISPR-Cas loci, in addition to recognized cas genes, also include genes that are not directly implicated in spacer acquisition, CRISPR transcript processing or interference. Here we comprehensively analyze sequences, structures and genomic neighborhoods of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
269
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(271 citation statements)
references
References 62 publications
2
269
0
Order By: Relevance
“…Specifically, they looked for protein families associated with genes encoding CARF domains, and found that genes for Csx3 are enriched in the gene neighborhoods of the CARF superfamily. 11 This suggests Csx3 and the previously identified CARF domain proteins may be functionally linked. One potential connection is the shared CARF domain common to each of these proteins.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…Specifically, they looked for protein families associated with genes encoding CARF domains, and found that genes for Csx3 are enriched in the gene neighborhoods of the CARF superfamily. 11 This suggests Csx3 and the previously identified CARF domain proteins may be functionally linked. One potential connection is the shared CARF domain common to each of these proteins.…”
mentioning
confidence: 90%
“…Bioinformatics efforts suggest that similar domains are also present in the Csm6 family, and other nonCas proteins associated with antiviral defense or a more general stress response. 11 These "CRISPR Associated Rossmann Folds," or CARF domains are frequently fused to potential effector domains that can include winged helix-turn-helix (wHTH) DNA binding domains, DNases of the restriction endonuclease fold and RNases of the RelE and HEPN families. 9,11-13 Collectively, these observations have led to the suggestion that the CRISPR associated Rossmann fold serves to provide ligand binding sites for nucleotides or modified nucleotides that may signal invading nucleic acid, and in cases where they are bound by a homodimer, the ligand may be 2-fold or pseudo-2-fold symmetric.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The remainder of the polypeptide, connected to the CARF domain via a short linker, is almost completely α-helical and is composed of two domains. The middle region of the TtCsm6 polypeptide chain (residues 191-292) consists of five α-helices and forms a right-handed solenoid domain previously denoted as the 6H domain (Makarova et al 2014). The C-terminal region of TtCsm6 (residues 293-450) comprises eight α-helices that form the HEPN domain.…”
mentioning
confidence: 99%